Embryonic endothelial evolution towards first hematopoietic stem cells revealed by single-cell transcriptomic and functional analyses - Hou, Siyuan; Li, Zongcheng; Zheng, Xiaona; Gao, Yun; Dong, Ji; Ni, Yanli; Wang, Xiaobo; Li, Yunqiao; Ding, Xiaochen; Chang, Zhilin; Li, Shuaili; Hu, Yuqiong; et al. (Cell research, 2020)
Hematopoietic stem cells (HSCs) in adults are believed to be born from hemogenic endothelial cells (HECs) in mid-gestational embryos. Due to the rare and transient nature, the HSC-competent HECs have never been stringently identified and accurately captured, let alone their genuine vascular precursors. Here, we first used high-precision single-cell transcriptomics to unbiasedly examine the relevant EC populations at continuous developmental stages with intervals of 0.5 days from embryonic day (E) 9.5 to E11.0. As a consequence, we transcriptomically identified two molecularly different arterial EC populations and putative HSC-primed HECs, whose number peaked at E10.0 and sharply decreased thereafter, in the dorsal aorta of the aorta-gonad-mesonephros (AGM) region. Combining computational prediction and in vivo functional validation, we precisely captured HSC-competent HECs by the newly constructed Neurl3-EGFP reporter mouse model, and realized the enrichment further by a combination of surface markers (Procr + Kit + CD44 + , PK44). Surprisingly, the endothelial-hematopoietic dual potential was rarely but reliably witnessed in the cultures of single HECs. Noteworthy, primitive vascular ECs from E8.0 experienced two-step fate choices to become HSC-primed HECs, namely an initial arterial fate choice followed by a hemogenic fate conversion. This finding resolves several previously observed contradictions. Taken together, comprehensive understanding of endothelial evolutions and molecular programs underlying HSC-primed HEC specification in vivo will facilitate future investigations directing HSC production in vitro.